Teachers’ perception of the implementation of project-based learning in early childhood education in Indonesia<subtitle>Project-Based Learning: a perspective from Indonesian early childhood educators</subtitle> - Siti Aisyah; Dian Novita (Cogent Education)
Project-based learning (PjBL) is a valuable approach that promotes a love of learning, cultivates critical and creative thinking skills in children, and offers proven benefits for educators, ultimately improving early childhood education outcomes. This study aims to address the following research questions: (1) What are the perceptions of early childhood educators in Indonesia regarding the implementation of PjBL? (2) How do these perceptions differ based on educators’ teaching experience and familiarity with PjBL? (3) What role does school contextualization, including infrastructure, facilities, and administration, play in effective PjBL implementation? (4) How does parental involvement influence PjBL implementation as seen by educators? To investigate these questions, this study utilizes a quantitative strategy employing a survey method. The research findings indicate that Indonesian early childhood educators possess favorable perspectives on the implementation of Project-Based Learning (PjBL) and report beneficial teaching experiences following four years of practice. Furthermore, the study underscores the critical importance of the school context—encompassing infrastructure, facilities, and administrative support—in facilitating effective PjBL implementation. Additionally, the findings highlight the significant influence of parental involvement, wherein parents contribute to the success of children’s PjBL experiences by fostering a supportive home learning environment, enhancing motivation and interest, and supplying essential resources. These findings suggest that parents play a crucial role in facilitating their children’s success with PjBL. While most teachers have a positive view of PjBL, recognizing its benefits in skill enhancement, they also encounter challenges such as limited training, resources, and classroom management, which warrant further investigation. Educators with more than four years of experience with PjBL tend to view certain aspects more positively, emphasizing the importance of adequate practical preparation.